1996
DOI: 10.1128/jvi.70.12.8270-8276.1996
|View full text |Cite
|
Sign up to set email alerts
|

Genetic correlates of in vivo viral resistance to indinavir, a human immunodeficiency virus type 1 protease inhibitor

Abstract: Indinavir (IDV) (also called CRIXIVAN, MK-639, or L-735,524) is a potent and selective inhibitor of the human immunodeficiency virus type 1 (HIV-1) protease. During early clinical trials, in which patients initiated therapy with suboptimal dosages of IDV, we monitored the emergence of viral resistance to the inhibitor by genotypic and phenotypic characterization of primary HIV-1 isolates. Development of resistance coincided with variable patterns of multiple substitutions among at least 11 protease amino acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
111
1
2

Year Published

1997
1997
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 372 publications
(119 citation statements)
references
References 31 publications
5
111
1
2
Order By: Relevance
“…It has been shown that mutations at codon 10, 63, or 71 compensated for a reduced viability of HIV-1 variants with a primary resistance mutation at codon 82 [78,79]. High-level resistance caused by the accumulation of primary and secondary mutations can lead to clinically significant reductions in drug susceptibility [80,81]. A mutation at codon 63 has been shown to be the most polymorphic mutation in the protease gene [82].…”
Section: Mechanisms Of Resistance To Pismentioning
confidence: 99%
“…It has been shown that mutations at codon 10, 63, or 71 compensated for a reduced viability of HIV-1 variants with a primary resistance mutation at codon 82 [78,79]. High-level resistance caused by the accumulation of primary and secondary mutations can lead to clinically significant reductions in drug susceptibility [80,81]. A mutation at codon 63 has been shown to be the most polymorphic mutation in the protease gene [82].…”
Section: Mechanisms Of Resistance To Pismentioning
confidence: 99%
“…This has been the experience in HIV therapy, especially with the HIV-protease inhibitors. [35][36] Thus, in hepatitis B where two antiviral agents, which have overlap- NOTE. Examples of mutations reported in HBV polymerase protein associated with drug resistance to Lamivudine and Famciclovir with the corresponding changes in HBsAg.…”
Section: For Hbv Infection Would a Combination Of Famciclovir And Lamentioning
confidence: 99%
“…Monotherapy trials demonstrated up to a 3.1log 10 decline in HIV-1 RNA levels (Stein et al 1996). The genetic correlates of in vivo resistance revealed variable patterns of multiple substitutions, indicating that resistance evolved through multiple pathways during ongoing replication; however, resistant isolates typically had substitutions at codons 46 and/or 82 (Condra et al 1996).…”
Section: Clinical Use Of Hiv-1 Protease Inhibitors and Evolution Of Rmentioning
confidence: 99%